Reconstructing Extensional Basin Architecture and Provenance in the Marrakech High Atlas of Morocco: Implications for Rift Basins and Inversion Tectonics. Issue 5 (7th May 2019) - Perez, Nicholas D.; Teixell, Antonio; Gómez‐Gras, David; Stockli, Daniel F.
Abstract: The Moroccan Atlas developed through a multiphase tectonic history including Permian‐Jurassic continental rifting and Cretaceous‐Cenozoic intracontinental shortening. New detrital zircon (DZ) U–Pb geochronologic results from the Ourika‐Zat region in the Marrakech High Atlas constrain the sediment provenance of prerift sediment sources and synrift and postrift basin fill. Prerift Precambrian‐Cambrian units contain Neoproterozoic DZ from the Pan‐African orogeny. Ordovician rocks contain diagnostic 0.95‐ to 1.28‐Ga DZ that are absent in the West African Craton, suggesting distal sediment sources. Permian rift basin fill contains Permian zircons that constrain maximum deposition age and diagnostic of northern Meseta domain sediment sources. New mapping and cross‐section construction demonstrate that Permian basin fill accumulated in a half‐graben above a southward dipping normal fault that likely guided subsequent inversion. Triassic rift basin fill thickens southward, above a likely northward dipping normal fault. The change in rift basin geometry was accompanied by catchment reorganization, the introduction of southern rift flank sediment sources, and subbasin integration. The southern catchment expanded to encompass Meso‐Archean rocks of the Reguibat Shield situated >800 km southward. Existing and new provenance results from postrift strata document onset of recycling of Atlas rift basin fill during the mid‐Cretaceous and before the onset of compressional inversion. These results highlight the interaction between deformation and sediment routing in an extensional basin and sediment dispersal patterns across continental margins during multiphase deformation. Stratigraphic, structural, and provenance characteristics reveal that the Atlas rift shares similarities with high‐angle and supradetachment basin models, emphasizing the diverse nature of extensional styles. Plain Language Summary: Throughout Earth history, the plates on the planet's surface have broken apart and collided together via plate tectonics. During these events, the Earth's crust can be deformed and eroded along linear zones called rifts (when plates break apart) and mountain ranges (when plates collide). Sediment produced during these events can be transported across the Earth's surface and preserved as sedimentary rocks in basins. This study investigates the Marrakech High Atlas Mountains of Morocco, where a rift formed and was followed by construction of a mountain range. The paper uses new geologic mapping, a cross section, and new studies of the preserved sedimentary rocks to investigate the Atlas Mountains spanning a Permian–Triassic rift, and Cretaceous to recent mountain building. The information gained from this study tells geoscientists that the earlier rift acted as a weakness in the Earth's crust. This weakness was used again as a site of compression during later collision. These results help geoscientists understand how continental crust forms and evolves during different phases of compression and extension. It also shows how the drainage patterns across continents can be sensitive to plate tectonic forces, which impacts the sediment and nutrients that eventually flow into the ocean. Key Points: Permian–Triassic half‐graben extensional basins guided deformation during Cretaceous‐Cenozoic inversion Sediment provenance evolved from northern to southern rift flank sources during Permian–Triassic rifting, with phases of catchment expansion and subbasin integration identified Sediment provenance results support early Cretaceous unroofing of High Atlas that predates onset of compressional inversion